Online fault compensation control method for ROV based on decoupling algorithm - Zhang, Nan (Frontiers in Mechanical Engineering, 2026)
IntroductionWith the increasing complexity of underwater operations, remotely operated vehicles systems face the dual challenges of multi-source interference and component failures in unknown environments.MethodsTo achieve high-precision control of remotely operated vehicles arms under fault conditions, this paper proposes an online fault compensation control method based on a decoupling algorithm. This method separates the end-effector position and attitude control of the master and slave arms through a pose decoupling algorithm, constructs an observer-based fault diagnosis mechanism, and combines H∞ robust control and online adaptive strategies to achieve dynamic compensation for combined sensor and thruster faults.ResultsThe results show that in dual-arm cooperative operation, the spatial trajectory tracking deviation of the robotic arm can be controlled within 4.3 mm, with a maximum deviation of 2.643 mm in the X-axis direction and a planning deviation of 3.075 mm in the Y-axis direction. Compared with backstepping fault-tolerant control and power sliding mode control, the method used in this study has a maximum deviation of only 0.01° in yaw angle control, a position control error reduced to 1.2 mm, and a maximum trajectory tracking error of 2.1 mm, which is significantly better than the comparative methods. Furthermore, the system can rapidly approach the desired posture within 50 seconds and maintains stable operation under various fault scenarios.DiscussionThis demonstrates that the proposed method can effectively improve the operational accuracy and fault “tolerance of remotely operated vehicles in complex environments, providing a new technology for solving the control problems of robot systems under fault conditions.”